Environmental and psychological influences on adolescents’ self-concept: teacher-student relationship as a moderator - Chen, Ting; Saibon, Jamalsafri (Institute of Advanced Engineering and Science, 2025)
Adolescence is a critical stage for the development of self-concept and psychological resilience. However, the impact of environmental and psychological factors on adolescents’ self-concept through psychological resilience has not been fully explored. Meanwhile, the discussion on whether the teacher-student relationship moderates the relationship between psychological resilience and self-concept is relatively rare. Based on cognitive-behavioral and social learning theories, this study collected data from 404 Chinese adolescents through a questionnaire survey. It employed partial least squares structural equation modeling (SEM) to test the hypotheses. The study found that environmental and psychological factors significantly influence adolescents’ psychological resilience, and psychological resilience mediates the relationship between environmental and psychological factors and self-concept. Moreover, the teacher-student relationship moderates psychological resilience and self-concept, particularly the positive teacher-student relationship, significantly promoting adolescents’ self-concept. This research highlights the critical influence of psychological resilience and teacher-student relationships in shaping adolescents’ self-concept. It provides empirical support for educational practice, highlighting the key role of environment, psychological factors, and good teacher-student relationships in adolescents’ mental health and self-concept development.